LEGAL CERTAINTY OF ULAYAT LANDSCERTIFICATION IN THE EMPOWERMENT OF NAGARI ASSETS IN WEST SUMATERA - Yulia Mirwati; Zahara; Neneng Oktarina; Surya Kamisli (INTERNATIONAL JOURNAL OF LAW, GOVERNMENT AND COMMUNICATION (IJLGC), 2018)
Nagari in West Sumatra is one of the titles for indigenous villages (Article 7 of Law No. 6 of 2014 on Villages) which is the spearhead of the lowest administrative regional administration. Nagari as the lowest government also has assets, both in the form of land and lain.Kepastian law of nagari assets in the form of land done through land certification. In general, the nagari asset in the form of ulayat land.With the empowerment of nagari assets in West Sumatra, will provide more free space for nagari in utilizing its assets, in an effort to improve the nagari economy, and or at the same time to provide legal certainty regarding the assets nagari.Untuk it need to be examined 1. How is the legal certainty of the certification of ulayat land in the empowerment of nagari assets in West Sumatra? 2. What are the constraints and solutions of legal certainty for the certification of ulayat land in Nagari asset empowerment in West Sumatra. This study uses "The juridical method of empirical, and normative. The result of the research shows that the land asset in West Sumatera nagari is not certified yet (there is no legal certainty). Obstacles to certification due to communal land do not include the object of certification (PP No. 24/1997).